The Literature on the History of Education in the First Decade of Soviet Power in Ukraine (According to Data Historiographical Michael Gordievskyi) - Tetyana Filimonova (Pedagogical Discourse, 2013)
The article is dedicated to  the scientific-pedagogical inheritance of not popular teacher Myhailo Ivanovich Gordievskyi. Biographical data of the teacher  as a many-sided scientist, researcher, publicman are described in the article. The author analyses  the scientific ideas which are dedicated to the problems of  history of pedagogics in the 1920-s.